Electrically Stimulated Eccentric Contractions during Walking Increases Oxygen Uptake - MATSUSE, HIROO; NAGO, TAKESHI; KAWAGUCHI, TAKUMI; IWANAGA, SOHEI; SHIBA, NAOTO; BEKKI, MASAFUMI; HASHIDA, RYUKI; TAKANO, YOSHIO (Kurume medical journal, 2019)
Neuromuscular electrical stimulation (NMES) is used to increase not only muscle strength but also whole-body metabolism. A hybrid training system (HTS) in which NMES is synchronized to voluntary exercise by an articular motion sensor may increase exercise load during aerobic walking exercise. We assessed the metabolic cost during walking exercise (5 minutes at 4 km/h and 5.6 km/h) on a treadmill simultaneously combined with HTS (HTSW) or without HTS (CON). We evaluated oxygen uptake ( VO·2) and heart rate (HR) during HTSW or CON on different days in fifteen subjects. The values ofVO·2 during HTSW at 4 km/h and 5.6 km/h were signifi cantly greater than those during CON (16.6 ± 1.85 ml/min/kg vs 15.3 ± 1.48 ml/min/kg; p < 0.05, 21.0 ± 2.17 ml/min/kg vs 19.4 ± 2.13 ml/min/kg; p < 0.01, respectively). The values of HR during HTSW at 4 km/h, 5.6 km/h were significantly greater than those during CON (106.7 ± 8.1 bpm vs 101.7 ± 10.3 bpm; p < 0.05, 126.5 ± 11.1 bpm vs 121.5 ± 12.5 bpm; p < 0.05, respectively). HTS added significantly to the exercise load by 8.3 ± 12.0% or 9.1 ± 9.9% during aerobic walking exercise at 4 km/h or 5.6 km/h, respectively. HTS might be useful for health promotion by increasing metabolic cost during aerobic walking exercise without increasing the perceived difficulty.